Rancang Bangun Alat Penjemur Kerupuk Udang Pintar dengan Mekanisme Penutup Otomatis dan Pewadah Otomatis di Desa Bunga Karang - Theo Maulana Al Aby; Nanda Nugraha (Jurnal Kemitraan Masyarakat, 2025)
Cracker drying process is considered inefficient because it still depends on weather factors and manual supervision, which can affect the quality of the production results. To overcome this, a smart shrimpcrackerdryingdevicebasedonan Arduino Uno microcontroller with an automatic closing mechanism and an automatic container has been designed and built. This system is equipped with a rain sensor and an LDR sensor to detect weather conditions around the device, as well as a DHT11 sensor to monitor humidity in the cracker storage container. In addition, an ultrasonic sensor is used to automatically regulate the movement of crackers into the storage container after the drying process is complete. A DC motor controlled by a BTS7960 driver functions to move the cover roof and the cracker transfer mechanism, while a limit switch is used to limit the motor movement.Based on the test results, this device can work automatically Shrimp crackers are one of the typical food products widely produced by the people of Bunga Karang Village, Tanjung Lago District, Banyuasin Regency. The traditional shrimp following changes in environmental conditions, thereby increasing the efficiency of the drying process and maintaining the quality of shrimp crackers produced by the residents of Bunga Karang Village.